Correlation of D-dimer level with the inflammatory conditions: a retrospective study - Bao, Wenchun; Qi, Xingshun; Li, Hongyu; Hou, Feifei; Zhang, Xintong; Wang, Ran; Guo, Xiaozhong (AME Medical Journal, 2017)
Background: D-dimer is produced during the fibrinolysis. A retrospective study was conducted to assess the association between D-dimer and inflammatory parameters in unselected patients with digestive diseases. Methods: All patients who were consecutively admitted to our department between January 2016 and October 2016 and underwent D-dimer tests were included. Spearman non-parametric tests and Pearson chi-square tests were performed to evaluate the correlation of D-dimer with inflammatory parameters. The correlation coefficients were calculated. Results: Overall, 205 patients (112 males and 93 females) underwent 245 D-dimer tests. Among them, 9 patients were diagnosed with pancreatitis (8 males and 1 female) and 14 patients with liver cirrhosis (6 males and 8 females). In the overall analysis, D-dimer positively correlated with white blood cell (WBC), percentage of neutrophils, neutrophil count, C reaction protein, high sensitive C reaction protein (hsCRP), procalcitonin (PCT), and blood culture detection, but negatively correlated with lymphocyte percentage and lymphocyte count. In the subgroup analysis of patients with pancreatitis, D-dimer positively correlated with hsCRP and PCT. In the subgroup analysis of patients with liver cirrhosis, D-dimer positively correlated with WBC and hsCRP. Conclusions: D-dimer may reflect the inflammation conditions in unselected patients with digestive diseases. Further validation study should focus on the patients with specific digestive diseases.